IMPACT OF THIOPURINE DOSE IN COMBINATION THERAPY IN INFLAMMATORY BOWEL DISEASE. (22nd January 2022) - Nawaz, Ahmad; Glick, Laura; Li, Darrick; Gaidos, Jill; Proctor, Deborah; Al-Bawardy, Badr
Abstract: BACKGROUND: Multiple studies have suggested that combination therapy with thiopurines and anti-TNFs is superior to monotherapy in Crohn's disease (CD) and ulcerative colitis (UC). The optimal dose of thiopurines in combination therapy remains unclear. Our aim was to determine the impact of thiopurine dosing in combination therapy on the formation of anti-TNF antibodies and clinical outcomes in inflammatory bowel disease (IBD). METHODS: This is a single-center, retrospective cohort study of all IBD patients treated with thiopurine and anti-TNF combination therapy between 1/1/2012 and 11/1/2020. Therapeutic dose of thiopurines was defined as ≥ 1 mg/kg for 6-mercaptopurine (6-MP) and ≥ 2 mg/kg for azathioprine (AZA). The primary outcome was anti-TNF antibody formation between patients on a therapeutic dose of thiopurines (TD) versus those on non-therapeutic doses (NTD). Secondary outcomes included steroid-free clinical remission (SFCR), endoscopic healing (absence of ulcers/erosions in CD and Mayo endoscopic score ≤ 1 for UC), and normal serum C-reactive protein (CRP) (defined as ≤ 5 mg/L) in patients who were on combination therapy. Continuous variables were analyzed using an unpaired student's t-test. Categorical variables were analyzed using a chi-square test. RESULTS: A total of 108 patients were included. The median age was 31.5 years (range 13-69), and 58.3% were male (Table 1). A total of 81 patients (75%) were on infliximab (IFX), while 27 patients (25%) were on adalimumab (ADA). Therapeutic dose of thiopurine was used in 19% (n=21). TPMT activity data was available for 56 patients. Normal TPMT activity was noted in 100% (n=7) in the TD group vs. 81.6% (n=40) in the NTD group (p=0.10). There were no significant differences between the TD vs. NTD groups in terms of baseline and disease characteristics (Table 2). Anti-TNF antibody formation was observed in 31 patients (32.1% of patients on IFX and 18.5% of patients on ADA). In the TD group 23.8% developed anti-TNF antibodies vs. 29.9% (p=0.58) in the NTD group. The mean anti-TNF drug level was 19.8 ± 13.8 vs. 16.9 ± 15.5 μg/mL (p=0.44) in the TD vs. NTD groups, respectively. SFCR was observed in 57.1% vs. 60.9% (p=0.75) and 38.1% vs. 37.9% discontinued anti-TNF treatment in the TD vs. NTD groups, respectively. Endoscopic healing was achieved in 55 % vs 60% (p=0.69), and normal CRP was observed in 52.4% vs. 46% (p=0.27) in the TD vs. NTD groups, respectively. CONCLUSION: In our cohort, a therapeutic dose of thiopurine in combination therapy was not associated with lower rates of anti-TNF antibody formation compared to non-therapeutic doses. In addition, there were no significant differences in clinical outcomes such as normal CRP, SFCR, and endoscopic healing. Larger and prospective studies are needed to further elucidate the effect of thiopurine dosing in combination therapy for IBD.